2016
DOI: 10.21608/epsj.2016.33263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Arginine Supplementation on Some Hormones and Its Relation to Performance of Silver Montazah Chicken. 2- The Effect on Laying Duration.

Abstract: This experiment was conducted in Inshas Poultry Research Station, Ministry of Agricultural, Egypt, A total number of 420 hens and 105 cocks from Silver Montazah chickens (SM) (Egyptian local strain) flock were used to investigate the effect of dietary supplemental of arginine (Arg) levels on plasma nitric oxide (NO) and Insulinlike growth factor (IGF-I), testosterone (Testo) and luteinizing (LH) hormones concentrations, and their relation to productive and reproductive performance during laying period (28-40 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Liu et al [19] reported that the increase of serum IGF-1 concentration in geese corresponded to the improvement of egg weight and egg production rate and the reduction of feed conversion ratio. Sabry et al [20] observed that laying hens with higher serum IGF-1 concentration had a high egg production rate and egg mass and a low feed conversion ratio. Similarly, in this study, laying hens fed the diet supplemented with YGF251 increased the egg weight, egg mass, and serum IGF-1 concentration, whereas decreased the feed conversion ratio, in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [19] reported that the increase of serum IGF-1 concentration in geese corresponded to the improvement of egg weight and egg production rate and the reduction of feed conversion ratio. Sabry et al [20] observed that laying hens with higher serum IGF-1 concentration had a high egg production rate and egg mass and a low feed conversion ratio. Similarly, in this study, laying hens fed the diet supplemented with YGF251 increased the egg weight, egg mass, and serum IGF-1 concentration, whereas decreased the feed conversion ratio, in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Under in vitro conditions, AR stimulate sperm motility in different animal species (Radany et al, 1981;Patel et al, 1998) by increasing sperm metabolism (Srivastava et al, 2006). Dietary AR supplementation significantly increased semen volume, percentages of motile and live spermatozoa, and total sperm output/ ejaculate, while decreased abnormal sperm percentage in Silver Montazah cock (Sabry et al, 2016) and Fayoumi and Golden Montazah cockerels (Youssef et al, 2015) as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In chicken, level of testosterone and LH increased as affected by dietary AR supplementation (Sabry et al, 2016). In mice, AR had a role in testosterone anabolic action (Cremades et al, (2004) and AR supplementations improved the testicular function and semen quality in aged cocks (Abbaspour et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, it increases the transport of tyrosine and Trp to the brain (Banks, 2019). Tryptophan is not only an essential aminoacid for chickens, mainly used for protein synthesis, but also has various metabolic functions in the brain, such as the precursor of serotonin and melatonin (El-Slamoney et al, 2010;Khattak and Helmbrecht, 2019). Serotonin plays an important role in oocyte maturation, embryonic development, laying behavior, and improving intracellular Ca levels (Khattak and Helmbrecht, 2019;Alhajeri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%